Using chains for strength and conditioning - Berning, J. M.; Coker, C. A.; Adams, K. J. (Strength and Conditioning Journal, 2004)
To maximize gains in size, speed, and strength, coaches may utilize alternative methods of training. Anecdotal evidence exists suggesting the effectiveness of chains as a resistance training modality. This article discusses that evidence as well as practical methods of incorporating chains in a resistance training program.